Rivalry Forms in Interpersonal and Intergroup Interaction (Based on Foreign Studies) - V V Levchenko (Peoples' Friendship University of Russia (RUDN University), 2013)
The article analyses and systematizes the results of numerous empirical studies in foreign social psychology, dedicated to the comparison of various forms of rivalry (competition, cooperation) in interpersonal and intergroup interaction. It emphasizes the significant specification, made by J.M. Rabbie, concerning the interdependence of interpersonal and intergroup rivalry interrelations, that "the discontinuity hypothesis" of J. Schopler & C. Insko can be seen as a special case of a more general reciprocal interdependence hypothesis.